Propuesta para la implementación de un sistema de calidad bajo la normativa Iso 9001 para la empresa Grupo Pacheco - Tenelema Llumiluisa, Jonathan Paúl (2022)
The current research work had as purpose, to propose a Quality Management System under ISO 9001 standard for the Grupo Pacheco enterprise. In order to comply with the our study aims, they are made several visits to the enterprise for identifing the activities current situation, which it makes, and through a diagnosis evaluation diagnostic of the regulation, it could detect the deficiencies that presented by involved processes n the process to installation the internet. The study was performed, using descriptive research and the inductive method, by applying techniques, such as bibliography, interviews, CHECK LIST based on ISO 9001:2015 regulation, observation, among others. These techniques helped to get an information adequate collection, what allowed the proposed activities execution. Through the got results, they were achieved to identify the activities and processes, which make up the service provision by enterprise, furthermore, to the assessment, which is achieved, after completing the diagnosis assessment under the ISO 9001:2015 standard, thus demonstrating the little documentation that it has the enterprise to meet the requirements. For this, it is proposed a quality management system design, through the necessary documentation creation for compliance, with the regulation, with the purpose by allowing members of senior management to implement it, helping the enterprise achieves the established goals and establishing continuous improvement its activities, they remain as results, a quality service and satisfied customers.